2018
DOI: 10.1016/j.jare.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening mechanisms, deformation behavior, and anisotropic mechanical properties of Al-Li alloys: A review

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
151
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 498 publications
(159 citation statements)
references
References 106 publications
3
151
0
5
Order By: Relevance
“…The 1NN displacement is negative when the atomic radius of impurity is smaller than that of host atom (Al or Li), meaning that adding alloying elements is a potential way for controlling and designing the lattice mismatch between the precipitate Al 3 Li and matrix Al, which could be considered to increase the mechanical properties, eg. the strength of the Al-Al 3 Li interface in alloys [4,47].…”
Section: Site Preferences Of Transition Metals In L1 2 Al 3 LI Phasementioning
confidence: 99%
See 2 more Smart Citations
“…The 1NN displacement is negative when the atomic radius of impurity is smaller than that of host atom (Al or Li), meaning that adding alloying elements is a potential way for controlling and designing the lattice mismatch between the precipitate Al 3 Li and matrix Al, which could be considered to increase the mechanical properties, eg. the strength of the Al-Al 3 Li interface in alloys [4,47].…”
Section: Site Preferences Of Transition Metals In L1 2 Al 3 LI Phasementioning
confidence: 99%
“…Al-Li alloys are mainly used for aerospace industry due to the light weight and high strength. It has been known that the strengthening mechanism of Al-Li alloys is associated with the precipitation of the metastable ordered δ'-Al 3 Li phase, which has a L1 2 structure and forms as coherent spherical particles from the Al matrix [1][2][3][4][5][6]. It has been confirmed that δ'-Al 3 Li phase has a large intrinsic modulus, which could be the main reason of high elastic modulus in Al-Li alloys [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium as the lightest metal has been widely used in lithium batteries, pharmaceuticals, ceramics and alloy industry as a critical resource. The broad application of lithium products stimulated the growing demand for lithium dramatically.…”
Section: Introductionmentioning
confidence: 99%
“…The aluminum-lithium alloys have attractive applications in the aerospace industry owing to their lower density, better strength and higher stiffness comparing to the conventionally commercial 2xxx and 7xxx series aluminum alloys [1][2][3][4][5][6][7][8]. However, insufficient plasticity, toughness and obvious anisotropy prevent their universal uptake [9].…”
Section: Introductionmentioning
confidence: 99%